1988
DOI: 10.1084/jem.168.1.279
|View full text |Cite
|
Sign up to set email alerts
|

Complement receptor type 3 (CR3) binds to an Arg-Gly-Asp-containing region of the major surface glycoprotein, gp63, of Leishmania promastigotes.

Abstract: Leishmania is an obligate intracellular parasite that survives within the phagolysosomes ofits vertebrate hosts' macrophages (1-3). Once the promastigote form ofthe parasite is introduced into the host tissue by a feeding sandfly, it must gain entry into a macrophage in order to survive and develop into the amastigote form. The initial attachment of Leishmania promastigotes to the macrophage is receptor mediated (4-6), however, the identity ofthe ligands on the parasite and their complementary receptors on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
1
7

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(113 citation statements)
references
References 46 publications
6
99
1
7
Order By: Relevance
“…CD11a contributes to the homotypic binding of lymphocytes (21), and to the heterotypic binding of T to B cells (8) and of CTL to their targets (3). CD11b mediates the adhesion of phagocytes to particles opsonized with C3bi (28) and other ligands (34)(35)(36), and to endothelium (37).…”
Section: Resultsmentioning
confidence: 99%
“…CD11a contributes to the homotypic binding of lymphocytes (21), and to the heterotypic binding of T to B cells (8) and of CTL to their targets (3). CD11b mediates the adhesion of phagocytes to particles opsonized with C3bi (28) and other ligands (34)(35)(36), and to endothelium (37).…”
Section: Resultsmentioning
confidence: 99%
“…parasites with normal mouse serum is not necessary for inhibition (data not shown), suggesting that CR3 ligation is not mediating the interaction. However, MP are able to synthesize complement components (McPhaden and Whaley, 1993) that opsonize parasites even in serum-free conditions (Wozencraft et al, 1986) and parasite components have been suggested to bind CR3 directly (Russell and Wright, 1988;Talamas-Rohana et al, 1990;Kedzierski et al, 2004). Furthermore, the repetitive structure and glycan modifications associated with many Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
“…This receptor recognizes a wide variety of structurally unrelated molecules from either the host (e.g., complement C3 fragment [iC3b], intercellular adhesion molecule-1 [ICAM-1], or fibrinogen) or pathogens (e.g., Bordetella pertussis filamentous hemagglutinin and Leishmania gp63) (Diamond et al, 1993;McGuirk and Mills, 2000;Russell and Wright, 1988). Similarly to other integrins, CR3 integrates the intracellular and extracellular environments through inside-out and outside-in bidirectional signaling.…”
Section: Cr3 In Innate Immunitymentioning
confidence: 99%